2014
DOI: 10.1517/13543784.2014.934808
|View full text |Cite
|
Sign up to set email alerts
|

The role of arginine and the modified arginine deiminase enzyme ADI-PEG 20 in cancer therapy with special emphasis on Phase I/II clinical trials

Abstract: The results of current studies are promising but do not give unequivocal answers and so it is impossible to recommend arginine or its enzyme ADI as a therapeutic. In the opinion of the authors, further identification of arginine-dependent malignant tumors and their metabolism should be investigated. Furthermore, the use of these chemicals, in combination with other chemotherapeutics drugs, should be investigated and indeed may improve the success of arginine-depleting enzymes such as pegylated ADI (ADI-PEG20).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 83 publications
1
26
0
Order By: Relevance
“…61 The bacterial origin of the molecule leads to neutralizing antibody formation and intramuscular injection site hypersensitivity reactions, limiting continued drug administration and a failure to sustain adequately low plasma arginine. 62,63 An alternative PEG human arginase has also been described, in which the enzyme cofactor has been replaced with cobalt to increase arginase activity, 52 but unfortunately seems in early preclinical studies to be significantly more toxic. Thus, the natural enzyme seems to be the best option.…”
Section: Discussionmentioning
confidence: 99%
“…61 The bacterial origin of the molecule leads to neutralizing antibody formation and intramuscular injection site hypersensitivity reactions, limiting continued drug administration and a failure to sustain adequately low plasma arginine. 62,63 An alternative PEG human arginase has also been described, in which the enzyme cofactor has been replaced with cobalt to increase arginase activity, 52 but unfortunately seems in early preclinical studies to be significantly more toxic. Thus, the natural enzyme seems to be the best option.…”
Section: Discussionmentioning
confidence: 99%
“…1 In addition, arginine starvation by using ADI-PEG20 (pegylated arginine deimidase) has shown promising results in tumors negative for ASS1 and currently it's been tested in clinical trials. 2 To exploit amino acid vulnerabilities for cancer therapy, one must first identify which amino acid is the most restrictive to the tumor. Amino acid demand and availability depend on many genetic and environmental factors such as extracellular free amino acid supply, amino acid uptake, synthesis and degradation, protein synthesis rate, the divergent use of amino acid for energy, and tRNA levels.…”
Section: Monitoring Amino Acid Deficiencies In Cancermentioning
confidence: 99%
“…2 In normal cells, Arg depletion results in G1 cell cycle arrest, which is abrogated after subsequent administration of exogenous arginine. 3 By contrast, tumor cells lacking Arg synthesis do not have the capacity to regrow and proliferate again. Hence, this auxotrophy may be their Achilles' heel.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, this auxotrophy may be their Achilles' heel. 3 Arg auxotrophy results from genetic or epigenetic (mostly by methylation) inactivation of the argininosuccinate synthetase 1 (ASS1) gene 4 and it is primarily found in tumors associated with chemoresistance and a poor clinical outcome-such as melanoma, hepatocellular carcinoma, and pancreatic cancer. 5 In the only prior study, glioblastoma multiforme (GBM), a deadly primary brain malignancy, has been identified as another target for Arg-depleting therapeutic strategies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation